Asplenium coronatum (Aspleniaceae), a new fern species from the Brazilian Atlantic Forest - Reis, Atiles; Lino, Vanessa; Massi Mynssen, Claudine; Da Silva Sylvestre, Lana (Phytotaxa, 2022)
A new fern species, Asplenium coronatum (Aspleniaceae), endemic to the Atlantic Forest is described. This species belongs to the Asplenium serratum complex, which comprises species that have simple, entire laminae with free veins ending near the margin and no marginal vein. Asplenium coronatum is distinguished from A. serratum by its large scales, which are often more than 20 mm long and have regularly thick cell walls, and laminae with an irregular, entire to slightly crenulate margin and acute to acuminate-caudate apex, commonly bearing a proliferous tip.